Application of Aspen Plus to Modelling and Simulation of Neem Seed Oil Extraction - USMAN, John Goji; OKONKWO, Paul Chidi; MUKHTAR, Bello; BABA, Abdul (ABUAD Journal of Engineering and Applied Sciences, 2024)
The demand for neem oil keeps on increasing due to its wide applications in pharmaceutical, agro–allied industries, cosmetics and soap production. To avoid wastage of material and safety of operation and personnel, the designed plant must be simulated to predict its performance before actual construction. The property method based on the non–random two–liquid (NRTL) model of Aspen Plus V12 was used to simulate the designed plant and its predicted performances were 87.13% and 99.60% for quantity of neem oil to be obtained from the evaporator and quantity of solvent (ethanol) recovery from the condenser as against 85.93% and 94.93% of the practical result with 1.38% and 4.69% errors respectively. The extracted oil has iodine, acid and saponification values of 60.10 g I2/100 g, 4.2 mg KOH/g and 210.0 mg KOH/g respectively. The fatty acid compositions of oil are oleic acid, 46.61%; stearic acid, 11.83%; palmitic acid, 16.54%; 11 – octadecenoic acid, 3.58%; cis–vaccenic acid, 5.90%; cyclopropaneoctanal, 11.19%; squalene, 0.21% and trimethylsilyl–di(timethylsiloxy)-silane, 4.14%. Based on the quality and fatty acid composition of the extracted neem oil, it is highly recommended for cosmetics and soap production.